Assessment of Heat Mining Rate for Geothermal Exploitation from Depleted High-temperature Gas Reservoirs via Recycling Supercritical CO2. (May 2017) - Cui, Guodong; Zhang, Liang; Ren, Shaoran
Abstract: There is a great potential for the development of geothermal energy from high-temperature gas reservoirs. For a typical medium-size gas field, the estimated recoverable geothermal energy can be equivalent to over 20 million tons of standard coal. Especially, for depleted high-temperature gas reservoirs, their existing wells and surface facilities can also be fully utilized to reduce investment cost, and it is proposed that supercritical CO2 (SCCO2 ) can be used for geothermal recovery in favour of its high heat transmission and flow capabilities. In this paper, a simulation model of geothermal exploitation from gas reservoirs was established in order to assess the heat mining rate via recycling SCCO2 . The simulation results show that for a typical gas reservoir with a volume of 1000 m × 500 m × 50 m at a temperature of 130 °C, the heat mining rate of one injector-producer pair can be maintained at 5 MW with SCCO2 recycling rate of 3000 t/day over 30 years. The influences of various parameters on geothermal recovery were also investigated using the model, including the initial temperature, the injection-production pressure difference, and the initial permeability of the gas reservoir.